Public Perceptions of Mosquitoes and Mosquito Control - Shelli Rampold; Ricky Telg; Alena Poulin; Sandra Anderson; Angela Lindsey; Ashley McLeod-Morin; Phillip Stokes (EDIS, 2020)
The Prevent & Protect publication series focuses on the creation of different material formats to resonate with various audiences and ways to maximize efficacy in communicating about mosquito-related risks and mosquito control topics to the public. This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication provides a background of public opinion on various aspects of mosquito control covered in the Prevent & Protect campaign. Written by Shelli Rampold, Ricky Telg, Alena Poulin, Sandra Anderson, Angela B. Lindsey, Ashley McLeod-Morin, and Phillip Stokes.